Unravelling Indian Culture : The essence of Bharat Modern India - Bhagat, Madhukar Kumar (New Delhi : GKP, 2024)
Unravelling Indian Culture: The Essence of Bharat takes the reader on a memorable journey through the rich and colourful tapestry of India's glorious cultural traditions and achievements.The carefully compiled and curated text spread over three volumes, is illumined by nearly 1700 photographs.Such a wide array of photographs imparts a clear and unfiltered view of the myriad elements of Indian culture. They are thus integral to the very concept of this series, which is to offer the common reader, a lucid understanding of the range, depth and intricacies of our rich cultural ethos. The photographs also take these three volumes into the category of an illustrated work on Indian culture.This volume (the third volume of the series) is on Modern India and comprises eleven chapters; starting from Chapter 14 and ending in Chapter 24.The first chapter of this book (Chapter 14) chronicles the emergence of modern Indian culture that begins with different shades of early European influence. It moves on to a defining British cultural phase and culminates in the post-independent cultural mosaic of modern India. The far-reaching impact of socio-religious reforms and reformers in modern India is covered in Chapter 15. The next three chapters, namely, Chapters 16, 17 & 18 take the reader through the fascinating evolution of paintings, music and dances, respectively. Chapter 19 chronicles the world of Indian textiles and handicrafts, while Chapter 20 sheds light on India's literary giants and their achievements. The story of India's folk theatre and the rise and evolution of modern theatre is described in Chapter 21, while Chapter 22 is an exciting account of the long journey of Indian cinema. It chronicles the journey of Indian cinema from its nascent stage of the silent era to the mega-blockbusters of the 20th and 21st centuries.Chapter 23 is an account of the festivals and fairs of India, a very integral part of our vibrant culture.The last chapter namely, Chapter 24, chronicles the evolution of modern Indian architecture and the various influences that have shaped its growth.
Keywords: Art / General; Photography / General; Travel /General